Fatty Acid Synthase: A Metabolic Enzyme and Candidate Oncogene in Prostate Cancer - Migita, Toshiro (Oxford University Press, 2009)
BACKGROUND: Overexpression of the fatty acid synthase (FASN) gene has been implicated in prostate carcinogenesis. We sought to directly assess the oncogenic potential of FASN. METHODS: We used immortalized human prostate epithelial cells (iPrECs), androgen receptor–overexpressing iPrECs (AR-iPrEC), and human prostate adenocarcinoma LNCaP cells that stably overexpressed FASN for cell proliferation assays, soft agar assays, and tests of tumor formation in immunodeficient mice. Transgenic mice expressing FASN in the prostate were generated to assess the effects of FASN on prostate histology. Apoptosis was evaluated by Hoechst 33342 staining and by fluorescence-activated cell sorting in iPrEC-FASN cells treated with stimulators of the intrinsic and extrinsic pathways of apoptosis (ie, camptothecin and anti-Fas antibody, respectively) or with a small interfering RNA (siRNA) targeting FASN. FASN expression was compared with the apoptotic index assessed by the terminal deoxynucleotidyltransferase-mediated UTP end-labeling method in 745 human prostate cancer samples by using the least squares means procedure. All statistical tests were two-sided. RESULTS: Forced expression of FASN in iPrECs, AR-iPrECs, and LNCaP cells increased cell proliferation and soft agar growth. iPrECs that expressed both FASN and androgen receptor (AR) formed invasive adenocarcinomas in immunodeficient mice (12 of 14 mice injected formed tumors vs 0 of 14 mice injected with AR-iPrEC expressing empty vector (P < .001, Fisher exact test); however, iPrECs that expressed only FASN did not. Transgenic expression of FASN in mice resulted in prostate intraepithelial neoplasia, the incidence of which increased from 10% in 8- to 16-week-old mice to 44% in mice aged 7 months or more (P  = .0028, Fisher exact test), but not in invasive tumors. In LNCaP cells, siRNA-mediated silencing of FASN resulted in apoptosis. FASN overexpression protected iPrECs from apoptosis induced by camptothecin but did not protect iPrECs from Fas receptor–induced apoptosis. In human prostate cancer specimens, FASN expression was inversely associated with the apoptotic rate (mean percentage of apoptotic cells, lowest vs highest quartile of FASN expression: 2.76 vs 1.34, difference = 1.41, 95% confidence interval = 0.45 to 2.39, P(trend) = .0046). CONCLUSIONS: These observations suggest that FASN can act as a prostate cancer oncogene in the presence of AR and that FASN exerts its oncogenic effect by inhibiting the intrinsic pathway of apoptosis.